2022
DOI: 10.1021/acschembio.2c00057
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperlipidemic Activity of Gut-Restricted LXR Inverse Agonists

Abstract: Hyperlipidemia and increased circulating cholesterol levels are associated with increased cardiovascular disease risk. The liver X receptors (LXRs) are regulators of de novo lipogenesis and cholesterol transport and have been validated as potential therapeutic targets for the treatment of atherosclerosis. However, efforts to develop LXR agonists to reduce cardiovascular diseases have failed due to poor clinical outcomes-associated increased hepatic lipogenesis and elevated low-density lipoprotein (LDL) cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The unexpected observation that both 18 and 19 reduced the levels of low-density lipoprotein (LDL) cholesterol in plasma led to the hypothesis that this effect was driven by LXR in the intestine and/or liver. In a more recent study, the same group showed that, when dosed orally, compound 19 significantly suppresses the expression of intestinal sterol O -acyltransferase 2 (SOAT2), an LXR target gene that plays a key role in intestinal cholesterol reabsorption . Importantly, the resulting reduction in plasma LDL cholesterol and triglyceride levels takes place without modulating LXR target genes in the periphery.…”
Section: Non-absorbable Compounds Beyond Lipinski’s Rule Ofmentioning
confidence: 99%
“…The unexpected observation that both 18 and 19 reduced the levels of low-density lipoprotein (LDL) cholesterol in plasma led to the hypothesis that this effect was driven by LXR in the intestine and/or liver. In a more recent study, the same group showed that, when dosed orally, compound 19 significantly suppresses the expression of intestinal sterol O -acyltransferase 2 (SOAT2), an LXR target gene that plays a key role in intestinal cholesterol reabsorption . Importantly, the resulting reduction in plasma LDL cholesterol and triglyceride levels takes place without modulating LXR target genes in the periphery.…”
Section: Non-absorbable Compounds Beyond Lipinski’s Rule Ofmentioning
confidence: 99%
“…When examining the expression of intestinal genes that changed with SR9238 or SR9243 treatment (i.p.) we found that sterol O-acyltransferase 2 ( Soat2 ) gene expression was suppressed by ∼95% ( 86 ). This intrigued us given that SOAT2 has been a target for development of drugs to treat hypercholesterolemia and atherosclerosis ( 87 ).…”
Section: Nuclear Receptorsmentioning
confidence: 99%
“…Mice with an intestine specific KO of Soat2 are resistant to development of elevated plasma LDL-C on a high cholesterol diet ( 89 ) suggesting that targeting intestinal SOAT2 function or expression may be sufficient to provide this benefit. With our knowledge that SR9243 had no significant oral bioavailability we treated Ldlr null mice on a high cholesterol diet and observed that even though there was no liver or plasma exposure when SR9243 was administered orally, LDL-C was substantially decreased and was associated with repression of intestinal Soat2 expression and increased fecal cholesterol elimination ( 86 ). These data provided us with a clear mechanism that was driving the reduction in plasma LDL-C that we consistently observed as well as suggested that such compounds may hold utility in treatment of hypercholesterolemia, particularly in individuals that have mutations in the LDL receptor driving familial hypercholesterolemia.…”
Section: Nuclear Receptorsmentioning
confidence: 99%
“…Furthermore, in the context of chronic ethanol-induced liver disease, SR9238 attenuated fat accumulation, inflammation, and fibrosis [ 83 ]. Furthermore, SR9238 revealed an interesting reduction in LDL-C levels by suppressing the expression of sterol O-acyltransferase 2 (Soat2), suggesting its potential for treating hypercholesterolemia [ 84 , 85 ].…”
Section: Modulators Of Lxr Receptorsmentioning
confidence: 99%